2012
DOI: 10.1002/cjce.21687
|View full text |Cite
|
Sign up to set email alerts
|

Modelling carbon dioxide solubility in ionic liquids

Abstract: Solubility information for CO2 in different ionic liquids, ILs, in part can potentially be used to select a specific IL for the separation of CO2 from hydrocarbon fluids. Unfortunately, not all CO2–IL systems have been experimentally described at similar temperatures and pressures; therefore, a direct comparison of performance by process simulation is not always possible. In the extreme cases, the design of a CO2 separation process may require predicting the CO2–IL equilibria for which there are no available s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…However, this process is energy-intensive for the regeneration of solvent and is also plagued by corrosion problems. Currently, more attention has been focused on CO 2 absorption by ionic liquids (ILs) [7]. Nevertheless, the complicated design and synthesis for highly effective ILs and poor economics may be major obstacles to industrial applications and future developments [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, this process is energy-intensive for the regeneration of solvent and is also plagued by corrosion problems. Currently, more attention has been focused on CO 2 absorption by ionic liquids (ILs) [7]. Nevertheless, the complicated design and synthesis for highly effective ILs and poor economics may be major obstacles to industrial applications and future developments [8].…”
Section: Introductionmentioning
confidence: 99%
“…The emphasis in that work was placed on establishing the validity of the above computational scheme and looking for consistency in solubility trends rather than the optimization of the accuracy of the predicted solubility. When a larger dataset of CO 2 solubility measurements is included, the computed solubility using the above parameter values displays a significant bias, as recently pointed out . As a remedy, these authors suggested an additional pressure‐dependent parameter in the fit for μig*(T).…”
Section: Examples Of Molecular Modeling In Carbon Capturementioning
confidence: 92%
“…When a larger dataset of CO 2 solubility measurements is included, the computed solubility using the above parameter values displays a significant bias, as recently pointed out. [79] As a remedy, these authors suggested an additional pressure-dependent parameter in the fit for l ig à ðTÞ. We show below that it is unnecessary to introduce any additional parameters, either involving pressure-dependence or nonlinear dependence on temperature.…”
Section: Screening Of Ils For Co 2 Capture Efficiencymentioning
confidence: 99%
“…In addition, most technologies of CO 2 absorption are energy-intensive and are also plagued by corrosion problems, owing to the regeneration of solvent. Currently, more attention has been focused on CO 2 absorption by ILs [12]. Nevertheless, the complicated design and synthesis of high effective ILs and poor economics may be major obstacle to its industrial application and future development [13].…”
Section: Introductionmentioning
confidence: 99%